2014
DOI: 10.1152/ajpheart.00068.2014
|View full text |Cite
|
Sign up to set email alerts
|

α1- and α2-Adrenergic responsiveness in human skeletal muscle feed arteries: the role of TRPV ion channels in heat-induced sympatholysis

Abstract: The purpose of this study was to determine if heat inhibits α2-adrenergic vasocontraction, similarly to α1-adrenergic contraction, in isolated human skeletal muscle feed arteries (SMFA) and elucidate the role of the temperature-sensitive vanilloid-type transient receptor potential (TRPV) ion channels in this response. Isolated SMFA from 37 subjects were studied using wire myography. α1 [Phenylephrine (PE)]- and α2 [dexmedetomidine (DEX)]-contractions were induced at 37 and 39°C with and without TRPV family and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 40 publications
(76 reference statements)
1
28
0
Order By: Relevance
“…The results from this study, in conjunction with accumulating evidence in animal models (Kurjiaka & Segal, ; Gifford et al . ), points to a critical role for EDH, independent of NO, PGs, or K IR channels, in modulating sympathetic vasoconstriction during exercise.…”
Section: Discussionmentioning
confidence: 94%
“…The results from this study, in conjunction with accumulating evidence in animal models (Kurjiaka & Segal, ; Gifford et al . ), points to a critical role for EDH, independent of NO, PGs, or K IR channels, in modulating sympathetic vasoconstriction during exercise.…”
Section: Discussionmentioning
confidence: 94%
“…; Jendzjowsky & Delorey, ; Gifford et al . ; Mizuno et al . ), it is possible that in our study direct heating and/or increased shear stress‐induced NO produced local sympatholytic effects during insulin stimulation, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…TRPV4 channels are emerging as key plasmalemmal channels that mediates Ca 2+ influx and physiological functions in the endothelium (Fiorio Pla et al, ; Gao & Wang, ; Gifford et al, ; Ma et al, ; Sayed et al, ; Schierling et al, ; Sonkusare et al, ; Thodeti et al, ; Troidl et al, ). We have shown that the Ca 2+ increase in endothelial cells, arising from Ca 2+ entry via TRPV4 channels, may be amplified by a Ca 2+ ‐induced Ca 2+ release‐like mechanism acting at IP 3 Rs to generate propagating Ca 2+ waves.…”
Section: Discussionmentioning
confidence: 99%